2018
DOI: 10.1787/51837366-en
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the impact of businesses on people’s well-being and sustainability

Abstract: Businesses have a significant impact on people's economic and social conditions, as well as on environmental outcomes. This paper presents an overview of the various kinds of initiatives aimed at measuring or reporting on business' impact, or certain aspects of it. It shows that despite the proliferation of information and frameworks to measure these impacts, there is currently no common understanding and practice on how to assess the performance of businesses in different social and environmental areas. Build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Yet, most existing international standards often do not meet the specificities and needs of social and solidarity economy organisations. This is because they are generally not developed to measure the specific characteristics of social and solidarity economy organisations, such as their hybrid sources of income (Rawhouser, Cummings and Newbert, 2017 [41]) as well as inclusive governance and ownership (Salathé-Beaulieu, Bouchard and Mendell, 2019 [42]). A recent stocktaking exercise revealed that only a minority of business-oriented frameworks addresses dimensions such as work and life balance, personal security and subjective well-being (Shinwell and Shamir, 2018 [43]).…”
Section: International Discussion Around Standardisation Have Recently Coalesced Under the Impactmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, most existing international standards often do not meet the specificities and needs of social and solidarity economy organisations. This is because they are generally not developed to measure the specific characteristics of social and solidarity economy organisations, such as their hybrid sources of income (Rawhouser, Cummings and Newbert, 2017 [41]) as well as inclusive governance and ownership (Salathé-Beaulieu, Bouchard and Mendell, 2019 [42]). A recent stocktaking exercise revealed that only a minority of business-oriented frameworks addresses dimensions such as work and life balance, personal security and subjective well-being (Shinwell and Shamir, 2018 [43]).…”
Section: International Discussion Around Standardisation Have Recently Coalesced Under the Impactmentioning
confidence: 99%
“…40 Therefore, the question facing social and solidarity economy entities is not whether to collect user feedback, but how. This has led to the formation of intermediaries, like the Feedback Labs 41 and Listen4Good, 42 who specialise in harnessing beneficiary perception for non-profit and philanthropic organisations.…”
Section: Collecting Stakeholder Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that social and environmental impacts of firm operations and well-being outcomes should be built into firms' mission statements and business models, rather than being addressed as 'optional extras' (Dwyer, 2018). However, there is currently no common understanding and practice on how to assess the impacts of businesses on people's well-being and destination sustainability (Cazes et al, 2015;Shinwell & Shamir, 2018). Opportunities exist for tourism researchers to extend to businesses the well-being lens that is core to the Beyond GDP approach while exploring the advantages of different types of business models that firms can adopt consistent with this approach.…”
Section: Beyond Csrmentioning
confidence: 99%
“…These effects may be enhanced through advertising: a meta-analysis of the effect of advertising on household consumption expenditures showed that acute exposure to food advertising increased nutrient-deficient food intake in children (Boyland et al, 2016[68]; Kunkel, Castonguay and Filer, 2015 [69]). 43 The Product Impact Weighted Accounts framework by the Harvard Business School (Serafeim and Trinh, 2020 [90]) provides a way of accounting for the impacts of products in a broad sense, although its conceptualisation of consumer well-being is narrower than the OECD Well-being Framework.…”
mentioning
confidence: 99%